The Concept of Freedom and Its Boundaries: A Critical Look at Content, Methodology, Claims of Nigel Warburton’s Book - Ghadir Nasri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Nigel Warburton has noticed critical points in his work (Freedom: An Introduction with Readings, 2001) which are of paramount importance with regard to a deep visioning and conceptualization of freedom for the world, and today’s mankind. Regarding the significant role of freedom, the present article aims to review Warburton’s book with respect to policy and daily life. The main question of this research is the importance and necessity of debates on freedom, so this article tries to review his findings and critiques in that book. So, the writer of the article asks about new findings of Warburton and other writers whose works have been published in that work. According to this review, liberty (or freedom) is an ancient discussion and discusses issues concerning whose liberty, why liberty, how liberty, and the criteria of liberty in political philosophy. However, this an important achievement that Warburton has succeeded in bringing an abstract problem to politics and policymaking. Moreover, he, such as other analytic political philosophers, explains “liberty” in daily life. He has attached excellent studies written by well-known theoreticians on freedom. All of them have separated negative freedom from positive, and this separation is problematic in our research.